Closing the achievement gap in mathematics: Evidence from a remedial program in Mexico City - Emilio Gutiérrez; Rodimiro Rodrigo (Latin American Economic Review, 2014)
This paper evaluates the impact of an intervention targeted at marginalized low-performance students in public secondary schools in Mexico City. The program consisted in offering free additional math courses, taught by undergraduate students from some of the most prestigious Mexican universities, to the lowest performance students in a set of marginalized schools in Mexico City. We exploit the information available in all students' (treated and not treated by the program) transcripts enrolled in participating and non-participating schools. Before the implementation of the program, participating students lagged behind non-participating ones by more than a half base point in their GPA (over 10). Using a difference-in-differences approach, we find that students participating in the program observed a higher increase in their school grades after the implementation of the program, and that the difference in grades between the two groups decreases over time. By the end of the school year (when the free extra courses had been offered, on average, for 10 weeks), participating students' grades were not significantly lower than non-participating students' grades. These results provide some evidence that short and low-cost interventions can have important effects on student achievement.
Keywords: C23; I21; I28; O15; 330; Impact evaluation; Remedial education programs; Difference-in-differences estimators